The Role of Spending Behavior in Mediating the Influence of Financial Socialization and Reaction to Indebtedness among Malaysian Tertiery Students - Chia, Mei Si; Zuriadah Ismail; Rusliza Yahaya (International Business Education Journal, 2024)
Financial depression occurs when a person mismanages personal financial resources when engaging in financial planning or decision-making because it requires financial knowledge, financial awareness of financial products, and management skills. In Malaysia, the primary issues are the low level of financial literacy and the rising trend in the bankruptcy rate among the younger generation. Children and young adults may acquire financial attitudes, such as spending attitudes and responses to debt from their parents. Meanwhile, spending decisions might be influenced by financial awareness of financial products and peers due to the group effect. However, there is a very limited research on the role of spending behavior as a mediating variable for the influence of financial socialization and reaction to indebtedness. Hence, this study aims to assess the role of spending behavior in mediating the influence of financial socialization and reaction to indebtedness among tertiary students in Malaysia. This study includes 1800 tertiary students, with primary data is obtained through a structured questionnaire. This study employs partial least square structural equation modeling (PLS-SEM) for data analyses. The result indicates that spending behavior mediates the effects of parental influence, peer influence, and financial awareness on reaction to indebtedness. Furthermore, it is a competitive partial mediation of spending behavior between financial awareness and reaction to indebtedness. It indicates that the higher the level of financial awareness, the worse the reaction to indebtedness. It may be due to overconfidence in handling debt. However, high financial awareness and good spending behavior will contribute to a positive reaction when a person is indebted. As a result, this study recommends that tertiary students strengthen their financial literacy before graduation.